Towards a target employment rate within age and gender groups - Stanisław Jaworski; Zofia Zielińska-Kolasińska (Statistics in Transition New Series, 2021)
Quarterly employment rates in European countries are analysed in terms of the likelihood of achieving a specific employment rate within age and gender groups in a five-year horizon. The German employment rate serves as a benchmark for this research. The likelihood is estimated by a Monte-Carlo simulation based on the class of exponential smoothing models. The research presents a pessimistic prognosis of employment rates in European countries with respect to young and partly to older workers.
Keywords: 519; employment rate; exponential smoothing; forecasting; state space approach